Is there a court for Gaza? : A test bench for international justice - Meloni, Chantal (T. M. C. Asser Press, 2012)
"This volume asks: 'Is There a Court for Gaza?' The answer is a resounding yes. Indeed, there are at least two courts capable of addressing the armed conflict in Gaza that took place in December 2008 and January 2009: the International Court of Justice and the International Criminal Court. But neither of them has jurisdiction prima facie. The challenge, then, is to resolve the difficulties in establishing jurisdiction. Once this is done, the merits, which have only partially been addressed in the Goldstone Report, can be litigated. Even then, there are limits to the subject-matter jurisdiction that are likely to confine the judicial debate." From the foreword by prof. William Schabas, Professor of International Law, Middlesex University, London With contributions of: Robert W. Ash; Frank Barat; Jennifer Barnette; Eric David; Gabriele Della Morte; Gilles Devers; John Dugard; Richard Falk; Mireille Fanon Mendes-France; Vera Gowlland-Debbas; Michael G. Kearney; Flavia Lattanzi; Daniel Machover; Chantal Meloni; Daragh Murray; Giuseppe Palmisano; Alain Pellet; John Quigley; François Rigaux; Yaël Ronen; Yuval Shany; Raji Sourani; Gianni Tognini; Sharon Weill; Liesbeth Zegveld The Israeli attack on Gaza of 27 December 2008 - 18 January 2009 (so-called 'Operation Cast Lead'). started a critical debate at the international level on the alleged war crimes and possible crimes against humanity committed during and before the operation. In September 2009, the UN Fact Finding Mission on the Gaza Conflict presented its results in what became known as the 'Goldstone Report'. The UN General Assembly and the Human Rights Council, amidst high political pressure, endorsed the Report's recommendations, calling for prompt and adequate investigations by both sides to ensure accountability and justice for the victims of the conflict. In case of lack of proper domestic investigations and prosecutions, it was recommended to activate international justice mechanisms. The Prosecutor of the International Criminal Court opened a preliminary examination of the situation, but difficulties arose because of the uncertain status of the occupied Palestinian territory. The issue of the recognition of a State of Palestine is of extreme actuality and is currently under examination before the UN in New York (after President Abbas' UN bid for recognition, of September 2011). This book brings together for the first time essential documentation on the legal follow-up to the Gaza conflict and relevant critical literature by renowned international law professors and distinguished scholars and lawyers. The underlying question, whether there is a court for Gaza, can be seen as a test case for international justice, and sheds a light on the role of international institutions in the difficult mixture of law and politics that connotes international justice. The book is a useful tool not only for all parties to any extent involved or interested in the Israeli-Palestinian conflict, but at the same time for all those interested in the issue of accountability for international crimes and in the challenges that international justice is facing. Dr. Chantal Meloni is a researcher in international criminal law at the University of Milan, and an Alexander Von Humboldt scholar at the University of Berlin. She was based in Gaza during 2010, at the Palestinian Centre for Human Rights (PCHR). Dr. Gianni Tognoni, medical doctor, is Secretary-General to the Permanent Peoples' Tribunal, residing in the Lelio Basso Foundation, Rome, Italy. In his position, he is coordinating many research-projects in epidemiology, public health and human rights.